CO2 hydrate properties and applications: A state of the art - Sinehbaghizadeh, Saeid; Saptoro, Agus; Mohammadi, A.H. (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Global warming is one of the most pressing environmental concerns which correlates strongly with anthropogenic CO2 emissions so that the CO2 decreasing strategies have been meaningful worldwide attention. As an option, natural gas hydrate reservoirs have steadily emerged as a potent source of energy which would simultaneously be the proper places for CO2 sequestration if the method of CO2/CH4 replacement could be developed. On the flip side, CO2 hydrates as safe and non-flammable solid compounds without an irreversible chemical reaction would contribute to different industrial processes if their approaches could be improved. Toward developing substantial applications of CO2 hydrates, laboratory experiments, process modelling, and molecular dynamics (MD) simulations can aid to understand their characteristics and mechanisms involved. Therefore, the current review has been organized in form of four distinct sections. The first part reviews the studies on sequestering CO2 into the natural gas hydrate reservoirs. The next section gives an overview of process flow diagrams of CO2 hydrate-based techniques in favour of CO2 Capture and Sequestration & Utilization (CCS&U). The third section summarizes the merits, flaws, and different effects of hydrate promoters as well as porous media on CO2 hydrate systems at macroscopic and mesoscopic levels, and also how these components can improve CO2 hydrate properties, progressing toward the more feasibility of CO2 hydrate industrial applications. The final sector recapitulates the MD frameworks of CO2 clathrate and semiclathrate hydrates in terms of new insights and research findings to elucidate the fundamental properties of CO2 hydrates at the molecular level.